STRATEGI MANAJEMEN PENDIDIKAN MULTIBUDAYA DALAM MEWUJUDKAN MODERASI, TOLERANSI DAN INKLUSIVITAS DI LEMBAGA PENDIDIKAN - Azzahra, Luthfiyah; Muhammad Taufik Bintang Kejora; Fatimah Az Zahro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze multicultural education management strategies in realizing the values of moderation, tolerance, and inclusivity at SMKN 2 Karawang. The background of this research arises from the importance of managing diversity within schools as an effort to create a harmonious, fair, and respectful learning environment that embraces cultural and religious differences. The research employs a qualitative approach using the literature study (library research) method. Data were collected through an extensive review of books, scientific journals, academic articles, and previous studies relevant to multicultural education management and religious moderation. The findings indicate that the multicultural education management strategy at SMKN 2 Karawang is implemented through three main stages: planning oriented toward inclusive values, implementation through collaborative learning and intercultural activities, and continuous evaluation to strengthen moderate and tolerant attitudes within the school environment. This study concludes that multicultural education management serves as an effective approach to building an inclusive, open, and harmonious school culture.